Edukasi Pemanfaatan Tanaman Obat Lokal melalui Pembuatan Wellness Shot Jahe–Nanas untuk Meningkatkan Pengetahuan Masyarakat tentang Hipertensi - Resi Rizki Banjarani; Reza Laila Najmi; Efilia Meirita; Fitratul Wahyuni; Muhammad Azhari Herli (Universitas Mataram, 2026)
This community service activity aimed to enhance public knowledge and skills in managing hypertension through the utilization of local medicinal plants integrated with local wisdom and scientific approaches. The program was conducted in Kualu Nenas Village, Kampar Regency, involving 20 participants using a descriptive cross-sectional design. The intervention included health education, interactive discussions, and demonstrations on preparing a ginger–pineapple wellness shot as a functional beverage. The results showed that 100% of participants were aware of the benefits of medicinal plants and had experience in preparing herbal remedies, while 90% reported having medicinal plants in their home gardens and routinely using them for maintaining health. In addition, 95% of participants used herbal remedies to treat minor illnesses, and 100% acknowledged the existence of hereditary traditional knowledge in their families. However, only 65% of participants utilized herbal medicine for managing degenerative diseases such as hypertension. Post-education observations indicated increased understanding of hypertension, its risk factors, and the rational use of medicinal plants, supported by high participant engagement during the activities. The combination of participatory education and practical demonstration proved effective in bridging the gap between traditional knowledge and scientific understanding. Therefore, this approach is recommended as a sustainable promotive and preventive strategy to improve community health behavior and optimize the rational use of local medicinal resources.